2008
DOI: 10.1021/ac7026047
|View full text |Cite
|
Sign up to set email alerts
|

One-Step Sampling, Extraction, and Storage Protocol for Peptidomics Using Dihydroxybenzoic Acid

Abstract: The isolation and extraction of natively occurring signaling peptides (SPs) from tissue is a critical first step in characterizing these peptides. Recent studies have outlined several approaches designed to preserve and extract SPs from tissue. Here, we demonstrate a surprisingly simple method to extract SPs from tissue samples, ranging from cell clusters to brain punches to intact brain regions, using a matrix often employed in matrix-assisted laser desorption/ionization mass spectrometry-2,5-dihydroxybenzoic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 59 publications
1
39
0
Order By: Relevance
“…Since levels of these intermediates were expected to be low, we utilized the pituitary, a tissue rich in peptides, for our studies; although the neuropeptides in mouse pituitary have been well characterized, these reaction intermediates have not been detected [28], [31], [32]. Characterization of these amidation intermediates is challenging, not only because of their low levels compared to the fully processed peptides, but also due to the restrictions imposed by MS detection limits and dynamic range.…”
Section: Resultsmentioning
confidence: 99%
“…Since levels of these intermediates were expected to be low, we utilized the pituitary, a tissue rich in peptides, for our studies; although the neuropeptides in mouse pituitary have been well characterized, these reaction intermediates have not been detected [28], [31], [32]. Characterization of these amidation intermediates is challenging, not only because of their low levels compared to the fully processed peptides, but also due to the restrictions imposed by MS detection limits and dynamic range.…”
Section: Resultsmentioning
confidence: 99%
“…As developed by Romanova et al [33], the one-step protocol using saDHB solution was easy to perform (Fig. 1B).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Romanova et al [33] reported that the use of saturated DHB in aqueous solution could provide direct extraction of neuropeptides from neuronal tissues ranging from cellular clusters to intact brain. This one-step protocol is effective and can also be used for a long-term preservation of the neuropeptide extracts.…”
Section: Introductionmentioning
confidence: 99%
“…The requirement for substantial amounts of sample material frequently restricts peptidomics approaches to the analysis of either larger anatomically defined structures (whole brain) or pooled samples [7,8,1214,18]. An alternative that is suitable for quantitative profiling of minute individual samples is the single-step extraction of signal peptides using 2,5-dihydroxybenzoic acid (DHB), a commonly used matrix for MALDI MS [28]. The method is suitable for fractionation of peptides by capillary electrophoresis using DHB as a background electrolyte [29].…”
Section: Challenges That Drive New Developments In Quantitative Peptimentioning
confidence: 99%